2022
DOI: 10.1159/000527715
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Childhood Outcomes after Dextrose Gel Treatment of Neonatal Hypoglycaemia: Follow-Up of the Sugar Babies Randomized Trial

Abstract: <b><i>Introduction:</i></b> Dextrose gel is widely used as first-line treatment for neonatal hypoglycaemia given its cost-effectiveness and ease of use. The Sugar Babies randomized trial first showed that 40% dextrose gel was more effective in reversing hypoglycaemia than feeding alone. Follow-up of the Sugar Babies Trial cohort at 2 and 4.5 years of age reported that dextrose gel appeared safe, with similar rates of neurosensory impairment in babies randomized to dextrose or placebo ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…20 In addition, the approach of serial monitoring of the infant in the newborn nursery with intervention such as OGD therapy or NICU transfer only when indicated has been proven to be safe. 2,4,5 Other advantages, such as reduction in hospital expenses, have also been described. This reduction in healthcare costs allows for the reallocation of funds to other critical areas within the healthcare ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, the approach of serial monitoring of the infant in the newborn nursery with intervention such as OGD therapy or NICU transfer only when indicated has been proven to be safe. 2,4,5 Other advantages, such as reduction in hospital expenses, have also been described. This reduction in healthcare costs allows for the reallocation of funds to other critical areas within the healthcare ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of ODG was considered safe, with no adverse neurosensory outcomes observed in infants at 2 years, 4.5 years and 9 years of age. 2,4,5 Surprisingly, more recent studies investigating the potential advantages of ODG therapy have questioned its main bene ts. The primary goal of ODG therapy is to prevent the separation of newborns from their mothers by avoiding NICU admissions for intravenous therapies.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies showed no signi cant association of neonatal hypoglycemia with educational achievements in mid-childhood. (42,43) The long-term effects of using prophylactic dextrose gel were studied by prospectively following the participants of the hPOD study group. It was noted that the use of gel, compared with placebo, resulted in no signi cant difference in the risk of neurosensory impairment at 2 years corrected age.…”
Section: Discussionmentioning
confidence: 99%
“…Transitional neonatal hypoglycemia has characteristic features of hyperinsulinism, including the suppression of ketone production, the inhibition of glycogenolysis, and an exaggerated response to glucagon; it usually resolves within 36-48 h after birth [7]. Transi-tional neonatal hypoglycemia is not associated with adverse neurodevelopment [4], and treatment has not been shown to confer neurocognitive benefits [14,15]. Alternatively, the relatively underrecognized perinatal stress-induced hyperinsulinism is a prolonged form of non-genetic hyperinsulinemic hypoglycemia associated with perinatal stress (e.g., perinatal depression, small for gestational age, prematurity, and preeclampsia), characterized by the requirement for a high glucose infusion rate, high responsivity to diazoxide (a drug that suppresses insulin secretion via the activation of membrane K ATP channels), and eventual resolution within weeks to months after birth, confirmed by a safety fast [16,17].…”
Section: Transitional Neonatal Hypoglycemia and Perinatal Stress-indu...mentioning
confidence: 99%